Đặt a = x2 + 3x - 4 ; b = 2x2 - 5x + 3
=> 3x2 - 2x - 1 = a + b
khi đó phương trình đã cho có dạng: a3 + b3 = (a+ b)3
=> a3 + b3 = a3 + b3 + 3ab(a + b) => 3ab (a+b) = 0 => a= 0 hoặc b = 0 hoặc a = -b
Nếu a = 0 => x2 + 3x - 4 = 0 => x2 + 4x- x - 4 = 0 => (x - 1)(x + 4) = 0 => x = 1; -4
Nếu b = 0 => 2x2 - 5x + 3 = 0 => 2x2 - 2x - 3x + 3 = 0 => (2x-3)(x - 1) = 0 => x = 3/2; 1
Nếu a = - b => - (2x2 - 5x + 3) = x2 + 3x - 4 => 3x2 - 2x - 1 = 0 => 3x2 - 3x + x - 1 = 0 => (3x + 1)(x - 1) = 0 => x = -1/3; 1
Vậy x = 1; 3/2; -1/3; -4
Pt ⇔4x2+x+3+4xx+3−−−−√+2x−1+1−22x−1−−−−−√=0⇔(2x−x+3−−−−√)2−√−1)2=0⇔x=1⇔4x2+x+3+4xx+3+2x−1+1−22x−1=0⇔(2x−x+3)2+(2x−1−1)2=0⇔x=1